Whitewashing Nature: Sanitized Depictions of Biology in Children's Books and Parent–Child Conversation. Issue 6 (23rd April 2021) - Shtulman, Andrew; Villalobos, Andrea; Ziel, Devin
Abstract : The biological world includes many negatively valenced activities, like predation, parasitism, and disease. Do children's books cover these activities? And how do parents discuss them with their children? In a content analysis of children's nature books (Study 1), we found that negatively valenced concepts were rarely depicted across genres and reading levels. When parents encountered negative information in books (Studies 2–3), they did not omit it but rather elaborated on it, adding their own comments and questions, and their children (ages 3–11) were more likely to remember the negative information but less likely to generalize that information beyond the animal in the book. These findings suggest that early input relevant to biological competition may hamper children's developing understanding of ecology and evolution.